SnO2 nanowire anchored graphene nanosheet matrix for the superior performance of Li-ion thin film battery anode. Issue 1 (13th November 2014) - Thomas, Rajesh; Mohan Rao, G.
Abstract : All solid state batteries are essential candidate for miniaturizing the portable electronics devices. Abstract : All solid state batteries are essential candidate for miniaturizing the portable electronics devices. Thin film batteries are constructed by layer by layer deposition of electrode materials by physical vapour deposition method. We propose a promising novel method and unique architecture, in which highly porous graphene sheet embedded with SnO2 nanowire could be employed as the anode electrode in lithium ion thin film battery. The vertically standing graphene flakes were synthesized by microwave plasma CVD and SnO2 nanowires based on a vapour–liquid–solid (VLS) mechanism via thermal evaporation at low synthesis temperature (620 °C). The graphene sheet/SnO2 nanowire composite electrode demonstrated stable cycling behaviours and delivered a initial high specific discharge capacity of 1335 mAh g −1 and 900 mAh g −1 after the 50 th cycle. Furthermore, the SnO2 nanowire electrode displayed superior rate capabilities with various current densities.